A narrative inquiry into becoming attentive to relational ethics in recreation practice. Issue 5 (20th October 2019) - Dubnewick, Michael; Lessard, Sean; Clandinin, D. Jean; McHugh, Tara-Leigh
ABSTRACT: This article narratively inquires into the experiences of the first author and two recreation practitioners he worked alongside as they became wakeful to their relations as non-Indigenous people living alongside Indigenous peoples in a community garden project. The experiences shared highlight how they negotiated notions of professional competence tied to outcomes of programming, and how such narrow stories silenced the relational aspects of their practice. By inquiring into the experiences of each recreation practitioner, the purpose of this inquiry is to show how they made sense of living ethically in the field as a relational practice and how that shifted their relations in a community garden project.